WESTERN APPROACHES OF PRODUCING OF SOCIAL ADVERTISEMENT (COMPARATIVE ANALYSIS OF AMERICAN AND EUROPEAN SOCIAL ADVERTISEMENTS) - Soso Gazdeliani; Nino Chalaganidze (International Journal of Innovative Technologies in Social Science, 2024)
Social advertisement is the prosocial project of the past century having its roots from the Northern America. For years social advertisement had been passing through gradual changes. Despite of the fact that forms and means of expression, qualitative data were changing, its prosocial assignment and “noble” mission considering taking care over society, touching of social problems, trying to develop definite ways and recommendations to overcome challenges still remained unchangeable Within the social advertisement a problem is accumulated with its whole vividness. As a rule, it reflects alternative prospects and suggests possible ways of overcoming of such challenges. Accordingly, using of the social advertisement, being an instrument of prosocial activism, to receive a better social landscape is a finely approbated method. Western experience of the social advertisement is a conductor of the long-termed history, particularly in case of USA where efficient steps in this direction are constantly made since the period of the Second World War. In the present work we applied a comparative approach which enabled us to compare European and American trends of producing of social advertisements and to see definite similarities and different, on the first hand, on the continental level, and on another hand, by using the Georgian practice. The civilized world constantly makes an effort of resolving of social problems and their considering for the best interests of the society. Among multiple means, the stated aim serves to the periodic screening of the social advertisement; thus, a role of the traditional media, and contemporary digital platforms in this direction is priceless. A target of the present work, from the viewpoint of American and European peculiarities of producing of the social advertisement, is to distinguish key trends. As for the tasks, we made some steps to reach the aim, - reviewed the practice of producing of American and European Social advertisements, distinguished key similarities and differences, and finally, compared them.